BRAF-Mutated Non-Small Cell Lung Cancer: Current Treatment Status and Future Perspective - Yan, Ningning; Guo, Sanxing; Zhang, Huixian; Zhang, Ziheng; Shen, Shujing; Li, Xingya (Frontiers in Oncology, 2022)
V-Raf murine sarcoma viral oncogene homolog B (BRAF) kinase, which was encoded by BRAF gene, plays critical roles in cell signaling, growth, and survival. Mutations in BRAF gene will lead to cancer development and progression. In non-small cell lung cancer (NSCLC), BRAF mutations commonly occurs in never-smokers, females, and aggressive histological types and accounts for 1%-2% of adenocarcinoma. Traditional chemotherapy presents limited efficacy in BRAF mutated NSCLC patients. However, the advent of targeted therapy and Immune checkpoint inhibitors (ICIs) have greatly altered the treatment pattern of NSCLC. However, ICIs monotherapy presents limited activity in BRAF mutated patients. Hence, the current standard treatment choice for advanced NSCLC with BRAF mutations are BRAF targeted therapy. However, Intrinsic or extrinsic mechanisms of resistance to BRAF directed tyrosine kinase inhibitors (TKIs) can emerge in patients. Hence, there is still some problems facing to us for BRAF mutated NSCLC. In this review, we summarized the BRAF mutation types, the diagnostic challenges that BRAF mutations present, the strategies to treatment status of BRAF mutated NSCLC and resistance mechanisms of BRAF targeted therapy.